Konsep Theo-Democracy, Popular Vice Regency dan Faraghat dalam Wacana Islam dan Demokrasi - Mohd Zain, Mohd Izani (Jurnal Usuluddin, 2007)
The discourse of Islam and democracy emerges question whether both of them are compatible or not. The discussion also reflects the number of paramount thoughts like theo-democracy, popular vice regency and faraghat. All these discussions are debating the question of sovereignty, style of government and political freedom between the eyes of Islam and democracy. This article explores the conceptual of the-democracy, popular vice regency and faraghat advocate and support the element of democracy with one condition that the sovereignty of God (Allah) must be hightlighted at the first place.